A Remote Monitoring System to Optimize the Home Management of Oral Anticancer Therapies (ONCO-TreC): Prospective Training-Validation Trial - Alessandro Passardi; Flavia Foca; Orazio Caffo; Carlo Alberto Tondini; Alberto Zambelli; Roberto Vespignani; Giulia Bartolini; Francesco Giulio Sullo; Daniele Andreis; Marco Dianti; Claudio Eccher; Enrico Maria Piras; et al. (JMIR Publications, 2022)
BackgroundA platform designed to support the home management of oral anticancer treatments and provide a secure web-based patient-health care professional communication modality, ONCO-TreC, was tested in 3 cancer centers in Italy. ObjectiveThe overall aims of the trial are to customize the platform; assess the system's ability to facilitate the shared management of oral anticancer therapies by patients and health professionals; and evaluate system usability and acceptability by patients, caregivers, and health care professionals. MethodsPatients aged ≥18 years who were candidates for oral anticancer treatment as monotherapy with an Eastern Cooperative Oncology Group performance status score of 0 to 1 and a sufficient level of familiarity with mobile devices were eligible. ONCO-TreC consisted of a mobile app for patients and a web-based dashboard for health care professionals. Adherence to treatment (pill count) and toxicities reported by patients through the app were compared with those reported by physicians in medical records. Usability and acceptability were evaluated using questionnaires. ResultsA total of 40 patients were enrolled, 38 (95%) of whom were evaluable for adherence to treatment. The ability of the system to measure adherence to treatment was high, with a concordance of 97.3% (95% CI 86.1%-99.9%) between the investigator and system pill count. Only 60% (3/5) of grade 3, 54% (13/24) of grade 2, and 19% (7/36) of grade 1 adverse events reported by physicians in the case report forms were also reported in the app directly by patients. In total, 94% (33/35) of patients had ≥1 app launch each week, and the median number of daily accesses per patient was 2. Approximately 71% (27/38) and 68% (26/38) of patients used the app for messages and vital sign entering, respectively, at least once during the study period. ConclusionsONCO-TreC is an important tool for measuring and monitoring adherence to oral anticancer drugs. System usability and acceptability were very high, whereas its reliability in registering toxicity could be improved. Trial RegistrationClinicalTrials.gov NCT02921724; https://www.clinicaltrials.gov/ct2/show/NCT02921724